METHODOLOGICAL PRINCIPLES OF RESOURCE-ECOLOGICAL SAFETY PROVIDING IN THE REGION - Самойлік, М. С. (Scientific Progress & Innovations, 2014)
In the articles worked out methodological principles of resource-ecological safety providing in the region, it includes three stages: authentication of danger, determination of resource-ecological safety zones and forming of idea of problem decision; a choice of providing events of sufficient resource-ecological strength of region security (it comes true on the basis of optimization economic models and complex estimation of alternative scenarios of the naturally-economic potential use in the region that takes into account an ecological, economic and technological criterion); adjustment and concordance of decisions (it comes true on the basis of integral model of the economic- ecological systems development of the secondary material and power resources use in the region taking into account a regional specific).